The Influence of Service Quality and Train Comfort towards Passengers’ Satisfaction: A Case Study of KTMB ETS - Chia See Heng,; Abdul Hamid, Nor Aziati (Research in Management of Technology and Business, 2021)
The aim of this study is to identify the most significant service quality and train comfort factors that influence passenger satisfaction and to determine the current level of train comforts and service quality of KTMB ETS railway transport. The study adopted SERVQUAL model to evaluate rail service quality with focusing on five dimensions namely tangible, responsiveness, assurance, reliability and empathy. Besides, the study had been measured the comfort level of ETS from the four dimensions, noise, vibration, coach design layout and speed. Nine hypotheses were tested empirically based on the service quality model and train comfort model. The study used a validated online survey questionnaire to collect the data from 204 valid respondents of ETS passengers. Descriptive analysis and Spearman correlation were performed and analyzed the dimension of service quality and train comfort. The results showed all hypotheses were accepted and dimensions of service quality and train comfort have a positive relationship towards passenger satisfaction. In terms of service quality, reliability is the most significant factor that influences the passengers‘ satisfaction while the dimension of train comfort is vibration. The overall passenger satisfaction is high that ETS has showed the high current level of performance. This study would be beneficial to future study especially on more details on investigate the service quality and train comfort on railway transport system and provide the large improvement opportunity to the future researchers in determining the factors that influence the passengers‘ satisfaction especially on train comfort which lack of the current exist information. The finding of the study is limited to the context of ETS services under KTMB operation. The study could be expending to other EMU services by another operator using the developed instrument.